2002
DOI: 10.1088/0022-3727/35/7/306
|View full text |Cite
|
Sign up to set email alerts
|

Light emission ranging from blue to red from a series of InGaN/GaN single quantum wells

Abstract: In this paper, we describe the growth and characterization of InGaN single quantum wells with emission peaks in the blue, green, amber and red spectral regions, grown by metal-organic vapour phase epitaxy. Starting from the growth of a blue-emitting (peak ~430 nm) InGaN quantum well at 860°C the InGaN growth temperature was progressively reduced. The photoluminescence peak wavelength, measured at low temperature, shifts through the green and orange spectral regions and reaches 670 nm for an InGaN growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 21 publications
5
33
0
Order By: Relevance
“…For a variation of the InGaN growth temperature or In/Ga ratio high intensities in the longer wavelength region are achieved. We observe an exponentially decreasing PL intensity for longer wavelengths and an intensity ratio for the blue to red-orange emission around 12:1, similar to samples grown on sapphire [7].…”
Section: Movpe Growth Of Ingansupporting
confidence: 74%
“…For a variation of the InGaN growth temperature or In/Ga ratio high intensities in the longer wavelength region are achieved. We observe an exponentially decreasing PL intensity for longer wavelengths and an intensity ratio for the blue to red-orange emission around 12:1, similar to samples grown on sapphire [7].…”
Section: Movpe Growth Of Ingansupporting
confidence: 74%
“…There is also an increase in the strength of the phonon replicas relative to the zero-phonon recombination with increasing indium fraction. The trend of an increasing strength of the phonon replicas relative to the zero-phonon recombination with decreasing zero-phonon peak energy has also been observed in In 0.17 Ga 0.83 N/GaN quantum wells and quantum boxes of different dimensions [5,6] and in InGaN/GaN quantum wells with different indium contents [7].…”
Section: Methodsmentioning
confidence: 54%
“…Using this procedure, we found that all the spectra had phonon replicas separated by 91 meV, with no dependence on composition. Martin et al [7] have also reported LO phonon energies close to 90 meV independent of indium content in the quantum well.…”
Section: Methodsmentioning
confidence: 87%
“…6 These materials can emit light from the ultra-violet (UV) region through the visible and to the infra-red. 7 To produce highly efficient blue-emitting LEDs a series of thin InGaN layers are grown between several GaN layers creating a multi-quantum well structure, aiding carrier confinement and increased radiative recombination. Utilising hybrid inorganic/organic LED architectures offers the opportunity to combine the advantages of both technologies; the well-understood and high-performing electronic properties of inorganic LEDs with the broad, tunable emission of organic semiconducting materials.…”
Section: Introductionmentioning
confidence: 99%